2019
DOI: 10.1002/stem.3050
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Stem Cells and Cancer: Concise Review

Abstract: It is well established that the tumor microenvironment plays an important role in cancer development and progression. The tumor microenvironment is composed of neoplastic cells, endothelial cells, pericytes, adipocytes, fibroblasts and other connective tissue cells, extracellular matrix components, multiple stem and progenitor cells, and a diverse array of innate and adaptive immune cells [Nat Rev Cancer 2007;7:139–147]. Understanding the mechanisms behind cell–cell communication in the tumor microenvironment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 75 publications
0
24
0
Order By: Relevance
“…We have reported that the differentiation of adipose progenitors (APs), which are a type of mesenchymal stem cells, into myofibroblasts is dependent upon the primary cilium [ 12 ]. APs can also differentiate into CAFs and are found in several organs prone to cancer [ 13 , 14 ]. APs are particularly relevant in breast cancer since the adipose tissue is abundant in this organ and has been shown to be in direct contact with tumors.…”
Section: Introductionmentioning
confidence: 99%
“…We have reported that the differentiation of adipose progenitors (APs), which are a type of mesenchymal stem cells, into myofibroblasts is dependent upon the primary cilium [ 12 ]. APs can also differentiate into CAFs and are found in several organs prone to cancer [ 13 , 14 ]. APs are particularly relevant in breast cancer since the adipose tissue is abundant in this organ and has been shown to be in direct contact with tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence revealed that obesity promotes BC cells proliferation, migration, and invasion via modulating the levels of the adipokines secreted from obese ADSCs. 8,11,12,15 In the current study, we investigated the anti-proliferative activity of LG on obesity-associated BC. The impact of LG on modulating the adipokines in ADSCs and BC cells was also studied.…”
Section: Discussionmentioning
confidence: 99%
“…18 -20 Second, obesity alters the secretory profile of ADSCs to enhance cancer growth. 8,11,12,15,17 Compared to ADSCs isolated from lean women, ADSCs from obese subjects expressed significantly higher levels of leptin 8,12,15 and pro-inflammatory cytokines including IL-6, TNF-α, IL-12 and adhesion molecules. 11,21…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In breast, mammary tissue is embedded in the adipose tissue, which allows direct paracrine action of adipose-derived factors on mammary epithelial cells; thereby the stromal cells contribute to the regulation of cellular growth and differentiation of the mammary gland (18). However, adipose tissue-derived cells may also be a source for tumor stroma (12), and their secreted growth factors, especially IGF1, contribute to the growth of breast cancer cells (19). In this way, ASCs may play crucial role in the development of breast cancer and in the relapse of the disease as well.…”
Section: Discussionmentioning
confidence: 99%